Especialização Inteligente : as complementaridades relacionais da inovação ancorada nas macrorregiões de Lisboa e do Porto - Marques, Teresa Sá (2016)
The functional regions of Lisbon and Porto concentrate a large volume of employment (76% of the working population in mainland Portugal), of the productive capacity (81% of GDP) and Portuguese exports (90%). They also attract the countrys largest proportion of social, organisational and knowledge capital. They are the anchor regions of the processes of globalisation and the base of innovation of the Portuguese economy. The current European Unions innovation policy is rooted in the theoretical framework of intelligent specialisation, which drives economic strategies towards the promotion of the countries productive capacities, fostering regional comparative advantages. It is thus necessary to ascertain what each region is doing and if there are differentiated innovation systems. This study intends to identify the fields of specialisation and corresponding innovation sectors in the two functional macro-regions, highlighting the diversity of agents involved in the R&D processes. In methodological terms, we have explored the R&D+I projects that have been funded under the last Community support framework linked to the two macro-regions, based on the methodology of social network analysis.